2011
DOI: 10.1002/jclp.20772
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of restraints among youth in a psychiatric hospital: application of translational action research

Abstract: This study extends a translational action research program by applying a theoretically based measure of risk in predicting incidents of restraint among children and adolescents in a secure psychiatric hospital. Youth inpatients (N=149, ages 5-17) were assessed at intake for the presence of selected individual and contextual risk factors, and their involvement in critical incidents was tracked (i.e., number of episodes in which restraint was applied) for the remainder of their hospitalization. Models including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Association between a child or adolescent's history and being physically restrained. Physical restraint incidence is positively associated with multiple previous inpatient admissions (Delaney and Fogg, 2005;Furre et al, 2014Furre et al, , 2016, past trauma (Azeem et al, 2011;Delaney and Fogg, 2005;dosReis et al, 2010;Duke et al, 2014;Furre et al, 2014;Tompsett et al, 2011), and history of aggression (Crocker et al, 2010;Duke et al, 2014;Tompsett et al, 2011). Four studies associate a history of self-harm with increased likelihood of physical restraint (Delaney and Fogg, 2005;Furre et al, 2016;Sourander et al, 2002;Stewart et al, 2010).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Association between a child or adolescent's history and being physically restrained. Physical restraint incidence is positively associated with multiple previous inpatient admissions (Delaney and Fogg, 2005;Furre et al, 2014Furre et al, , 2016, past trauma (Azeem et al, 2011;Delaney and Fogg, 2005;dosReis et al, 2010;Duke et al, 2014;Furre et al, 2014;Tompsett et al, 2011), and history of aggression (Crocker et al, 2010;Duke et al, 2014;Tompsett et al, 2011). Four studies associate a history of self-harm with increased likelihood of physical restraint (Delaney and Fogg, 2005;Furre et al, 2016;Sourander et al, 2002;Stewart et al, 2010).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Delaney and Fogg (2005) report the most prevalent risky behaviours as agitation, threats, and staff-directed assault (most of which were extremely violent). A child or adolescent's aggressive acts (defined as harmful behaviour which may include deliberate intent to harm or injure another person (Bandura, 1973, cited in Suris et al, (2004) most frequently trigger the use of physical restraint (Crocker et al, 2010;Delaney and Fogg, 2005;dosReis et al, 2010;Duke et al, 2014;Furre et al, 2016;Muire-Cochrane et al, 2014;Pogge et al, 2013;Sourander et al, 2002;Stewart et al, 2010Stewart et al, , 2013Tompsett et al, 2011), with child-to-staff aggression being identified as a common precursor (Sourander et al, 2002;Tompsett et al, 2011). Studies also associate the use of physical restraint with 'lower level' behaviours (opposition, disinhibition, and absconsion) (Duke et al, 2014;Furre et al, 2016;Muir-Cochrane et al, 2014) as well as destruction of property (Furre et al, 2016;Muir-Cochrane et al, 2014).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The number of incidents found with this operationalization was 0.4 incidents a day. This figure is low, compared to the literature of critical incidents in both forensic child and adolescent psychiatry (1.1 critical incidents a day [22]), secured child and adolescent psychiatry (0.7-2.4 critical incidents a day [21,33]) as well as general child and adolescent psychiatry (0.6-2.4 incidents a day [1,16,18]). Although it is difficult to compare these prevalences, it is at least remarkable that the prevalence in our forensic population is not higher than the prevalence in general child and adolescent psychiatry.…”
Section: Prevalence Of Incidentsmentioning
confidence: 60%
“…A systematic review of the literature in general and forensic child and adolescent psychiatry by Tremmery and colleagues [13] found that in a regular child-and adolescent psychiatric ward the number of aggressive incidents ranged from 0.4 to 3.5 incidents per day, with 33-78 % of the admitted patients committing at least one aggressive act [1,[14][15][16][17][18]. A similar picture was found in a secured setting with 0.5-2.4 incidents per day and 27-54 % children or adolescents committing at least one aggressive act [19][20][21]. At a forensic adolescent psychiatric unit, 1.1 incidents per day were reported with 55 % of the population committing at least one aggressive act [22].…”
Section: Introductionmentioning
confidence: 85%
“…Studies explored staff,148–157 patient147 158–165 and mixed groups’166–173 views and experiences of seclusion and restraint. Nine studies focused on the processes surrounding seclusion and restraint 136 137 174–180. A further 16 studies evaluated interventions to reduce seclusion and restraint, with 13 finding significant decreases in rates of use,146 181–192 one reporting an increase193 and one reporting increased levels of knowledge about the topic area 194.…”
Section: Resultsmentioning
confidence: 99%